Analysis of thyroid involvement in children and adult Langerhans cell histiocytosis: An underestimated endocrine manifestation - Li, Yuanmeng; Chang, Long; Chai, Xiaofeng; Liu, He; Yang, Hongbo; Xia, Yu; Huo, Li; Zhang, Hui; Li, Naishi; Lian, Xiaolan (Frontiers in Endocrinology, 2022)
Background: Langerhans cell histiocytosis (LCH) is a rare disease caused by the clonal expansion of CD1a+/ CD207+ LCH cells. The thyroid involvement in LCH has mostly been described in case reports. Methods: We retrospectively evaluated the clinical characteristics, diagnosis, and treatment of 27 children and adult patients with thyroid LCH in our center between 2010 and 2021. Results: The incidence of thyroid LCH was 14.00% (7/50) in children and 10.10% (20/198) in adults, respectively. Among patients with thyroid involvement, 81.5% presented with diabetes insipidus (DI) as the first symptom, and 51.9% complained of neck swelling or mass. Children and adults with thyroid LCH had higher frequencies of the hypothalamic-pituitary axis (HPA) (children: 100% vs. 62.8%, P=0.05; adult: 95% vs. 42.1%, P<0.001), the lung (children: 85.7% vs. 25.6%, P=0.004; adult: 70% vs. 50.6%, P=0.099), and a lower frequency of bone (children: 14.3% vs. 55.8%, P=0.049; adult: 45% vs. 73.6%, P=0.008) involvement than patients without thyroid involvement. Patients with thyroid LCH had a higher frequency of primary hypothyroidism and a lower frequency of euthyroidism than patients without it. The two major types of ultrasound imaging were diffuse (55%) and nodular type (45%). The standardized uptake value of thyroid on 18-F-fluorodeoxyglucose positron emission tomography/computed tomography was 5.3–12.8. The diagnoses were confirmed using thyroid aspiration (54.5%) or surgery (45.5%). In addition, thyroid LCH combined with papillary thyroid carcinoma was not rare (2/27). Conclusion: Thyroid involvement in LCH is not rare. Furthermore, identifying thyroid involvement can facilitate the pathological diagnosis of LCH. Therefore, the possibility of thyroid LCH should be fully investigated in patients with DI, primary hypothyroidism, abnormal thyroid ultrasound results, and multi-system disease. In addition, thyroid aspiration can confirm suspected thyroid LCH. Finally, special attention should be paid to evaluating HPA and pulmonary involvement in thyroid LCH.